ПРОФЕСІЙНА КОМПЕТЕНТНІСТЬ І ПРОФЕСІЙНА КОМПЕТЕНЦІЯ В КОНТЕКСТІ ПІДГОТОВКИ МАЙБУТНІХ ДИЗАЙНЕРІВ (Pedagogy of Higher and Secondary Education, 2012)
У статті здійснено аналіз понять «професійна компетентність» і «професійна компетенція»; розкрито сутність поняття «професійна компетентність студентів-дизайнерів»; виокремлено професійну компетентність дизайнерів одягу та графічних дизайнерів.Ключові слова: професійна компетентність, професійна компетенція, студенти-дизайнери, підготовка дизайнерів.The article contains analysis of the terms “professional competency” and “professional authority”; it discovers the essence of the term “professional competency of design students”; puts emphasis on competency of clothes designers and graphic designers.Key words: professional competency, professional authority, design students, designers’ preparation.
Keywords: professional competency; professional authority; design students; designers’ preparation